A Thorough Systematic Review of the Diagnosis and Complication of Typhoid Fever in Children - Herka, Sri Nadra; Imelda (The Indonesian Journal of General Medicine, 2024)
Background: Salmonella enterica subspecies enterica serovar Typhi, sometimes known as Salmonella Typhi, is the bacterium that causes typhoid fever. It is a systemic infection that is mostly spread by contaminated food or water. Methods: Following PRISMA 2020 guidelines, this systematic review concentrated on full-text English literature published between 2014 and 2024. Editorials and review articles that appeared in the same journal as the submission were not accepted without a DOI. The literature was assembled using a variety of online resources, including ScienceDirect, PubMed, and SagePub. Result: Following a rigorous three-stage screening procedure, eight papers were found to have relevant links to our current extensive investigation. After that, the entire text was carefully examined, and these particular sections got extra focus. Conclusion: In summary, there is a significant amount of typhoid-related disease and mortality that may be avoided by implementing preventative measures, such as the introduction of a typhoid conjugate vaccine.